Παρουσία του Χαριλάου Τρικούπη : στα εκατόν πενήντα χρόνια από την γέννησή του - Κασιμάτης, Γρηγόριος (Τετράδια Ευθύνης, 1980)
Γιώργος Μαύρος, Γρηγ. Κασιμάτης, Κωνσταντίνος Καλλίας, Χαρίτων Κοριζής, Κώστας Σβολόπουλος, Παν. Φωτέας, Χάρης Λ. Καραμπαρμπούνης, Δημ. Μιχαλόπουλος, Γιώργος Πλουμίδης